Blind dates: Quasi-experimental evidence on discrimination - Per-Anders Edin; Jonas Lagerström (Institute for Labour Market Policy Evaluation (IFAU), 2006)
This paper provides evidence on discrimination in the hiring process. We use data generated from a “policy experiment” conducted at the Swedish public employment offices. Individuals registered at these offices can post their qualifications in a database available to employers over the Internet. Potential employers are free to search this database for job candidates and contacts between employers and candidates are recorded. We use two complementary identification strategies. First, since our data contain all information available to employers, we argue that selection on observables is viable. Second, we utilize the fact that individuals can choose not to reveal their name and gender to potential employers. Our main finding is that women have a 15 percent lower chance than men of getting contacted by employers and that this differential is fully explained by discrimination. Our results concerning ethnic discrimination are less conclusive, probably due to measurement errors.
Keywords: J71; 330; Blind dates; discrimination; Arbeitsvermittlung; Internet; Arbeitsmarktdiskriminierung; Schweden; Internetportal; Geschlechterdiskriminierung